The Effect Of Combination Sago And Katuk Leaves on Reducing Blood Sugar Level In Patients Diabetes Mellitus at North Luwu, Indonesia - Yudhira Azzahra; Ida Leida Maria; Andi Zulkifli; Ridwan Amiruddin; Muhammad Arsyad; Healthy Hidayanty (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background. Diabetes is a chronic metabolic disease characterized by increased blood glucoseor blood sugar levels. Treatment of diabetes patients can be done with non-pharmacological and pharmacological treatments. The combination of sago and katuk leaves has a pharmacological effect as an antidiabetic. Non-pharmacological treatment is a traditional treatment that is widely sought after by the Indonesian people because it is considered efficacious and relatively inexpensive. Sago plants are plants with a lower glycemic index than white rice so they can control blood sugar levels. Sago and katuk leaves are plants that have great potential to be developed in the North Luwu area. Although these two herbal plants are used separately, there has been no research that combines them as an alternative therapy for type 2 diabetes mellitus. Aim: This study aims to determine the effect of giving a combination of sago and katuk leaves on blood sugar levels in patients with type 2 diabetes mellitus. Method. This experimental study uses a quantitative research method with experimental research and a pretest-posttest with control group design. The location of this study is in the Masamba Health Center and Baebunta Health Center areas, North Luwu Regency. Sampling used purposive sampling technique, with a sample size of 60 respondents, 30 intervention groups and 30 control groups. Blood glucose levels were measured before and after 14 days of intervention. Data analysis used the Stata version 17 program which includes the T-Dependent, Wilcoxon and T-Independent tests. Results. The findings showed a significant difference in blood sugar levels in patients with diabetes mellitus before treatment with an average of 153.7 mg/dL and after treatment 148.6 mg/dL (p=0.000), with an average of 25.84 mg/dL for the intervention group and 6.34 mg/dL for the control group. Conclusion. There is an effect of giving a combination of sago and katuk leaves on blood sugar levels of patients with diabetes mellitus in the work areas of Masamba Health Center and Baebunta Health Center.